Clinical and laboratory parameters associated with Acute Kidney Injury in patients with Viperine Snake Bite: A Prospective Observational Study in Central Odisha - Kumar Thatoi, Pravat; Debasish Behera, Kumar; Mishra, Subhasri; Panda, Bhagyashree; Choudhury, Anurag; Barik, Priyaranjan; Prusty, Biswaranjan; Prusty, Biswaranjan; Pradhan, Jagannath; Pada Hota, Bibhu; Routray, Dipanweeta (Journal of Neonatal Surgery, 2025)
Aim: The aim of the present was to determine the clinical and laboratory parameters associated with AKI in patients with viperine snake bite in Central Odisha. Hypothesis: We hypothesize that there is a significant association between certain clinical and laboratory parameters and the development of AKI in patients with viperine snake bite in Central Odisha. Materials & methods: The General Medicine department of a tertiary teaching hospital in Central Odisha was the site of this prospective analytical investigation. This study was conducted between September 2020 and August 2021. In our study a total of 262 snake bite patients were scrutinized, out of which 137 snake bites were of neurotoxicity, 65 snake bites were of Viper, and 60 bites were of normal or dry bites. The study included 65 patients who were of viper bites. Out of 65 patients, 40 were male and 25 were female. Patients were included based on the inclusion and exclusion criteria. Conclusion: The presence of DIC and delay in hospital arrival following a snakebite are predictors of poor outcomes in patients with viperine snake bites developing AKI. Mortality can be prevented by early hospital arrival and administration of ASV.